The Role of Village Heads in Development Human Resources of Productive Age - Frederikus Antonius Mana; Syahruddin; Syahrabudin Husein Enala; Wa Ode Suriani (Papsel Journal of Humanities and Policy, 2024)
Improving the quality of public services is very important to improve community welfare and the competitiveness of human resources (HR). However, in remote areas such as Papua, unequal access to education, health and infrastructure is a serious challenge. This research focuses on the role of the Tof-Tof Village Government in developing productive age human resources. With a qualitative case study approach, data was collected through interviews, observation and documentation involving village officials and the community. The research results show that the Tof-Tof Village Government plays an important role as a motivator, facilitator and mobilizer in providing access to education, skills training and infrastructure development. Despite facing geographic constraints and limited resources, the initiative significantly improved the skills of local communities, with a 25% increase in competency scores among training participants. Challenges such as budget constraints and coordination were successfully overcome through innovative strategies. This research contributes to understanding the dynamics of human resource development in remote areas and provides policy recommendations for sustainable and inclusive development programs.